Sachse Laser in post-trauma urethral stricture. A valid alternative before urethroplasty. - Astrit Mustafa; Evisa Zhapa; Francesco Saverio Grossi (Albanian Journal of Trauma and Emergency Surgery, 2018)
Background: The most commonly used treatment modality for urethral strictures is the direct visual internal urethrotomy method according Sachse cold knife, but with low long-term success rate. Alternative method after failure is isurethroplasty with preputial flap or Buccal mucosa. The aim of this presentation is to report the efficacy of the Internal Urethrotomy with Holmium Laser (Sachse laser). Material and methods: We report three cases of urethral stenosis after trauma which treated with Internal Urethrotomy with Holmium Laser (Sachse laser) after failure of multiple treatments with Sachse cold knife. We evaluated and compared the uroflowmetry parameters before and after Sachse laser. Results: The average of uroflowmetry parameters before incision were: Q max 4.5 ml/sec, Q med 3 ml/sec. Voided Volume 323 cc, while after incision with Sachse laser were: Q max 30 ml/sec, Q med 12 ml/sec. Voided Volume 363 cc.No patients relapsed during follow-up time from 3 to 24 months. Conclusion: Even though these are only a few cases, we think that Sachse laser is a valid alternative after unsuccessful Sachse cold knife and before Urethroplasty, even in patients with urethral stricture after trauma.